Impact of punitivism and legitimate defense on the perception of ecuadorian citizen security - Arévalo Ramos , Jenny Mariela (2025)
The relationship between punitivism, legitimate defense and the perception of citizen security is a complex issue that reflects the tensions between the State's responses. The objective of this article is to analyze, from a documentary review, the impact of punitivism and legitimate defense on the perception of Ecuadorian citizen security. It was oriented towards the quantitative research approach; documentary type, with a non-experimental design and the positivist paradigm. Databases were analyzed: Scielo, Dialnet, as well as Ecuadorian norms and laws. The results were that according to the Comprehensive Criminal Organic Code (COIP), self-defense is a right that allows citizens to act to protect themselves against imminent aggression. It is concluded that the judicial and security system in Ecuador is overloaded and faces serious limitations in its ability to translate criminal sanctions into a tangible improvement in the perception of security.